Impact of shape on pedestal characteristics in the wide pedestal quiescent H-mode in the DIII-D tokamak. (17th February 2021) - Wilks, T.M.; Morton, L.A.; Kriete, D.M.; Knolker, M.; Snyder, P.B.; Barada, K.; Paz-Soldan, C.; Rhodes, T.; Burrell, K.H.; Chen, X.; Hughes, J.W.
Abstract: Experiments on the DIII-D tokamak have advanced the operational limits of wide pedestal quiescent H-mode plasmas towards increased ITER relevance by simultaneously demonstrating well-matched plasma shape and net zero injected torque. Wide pedestal QH-modes are a compelling candidate regime for a future power producing device because they maintain a stationary pedestal without ELMs via additional edge transport. The pedestal is wider than what would be predicted from kinetic ballooning mode physics due to enhanced edge transport generated by broadband turbulence, a limit cycle oscillation, or some combination thereof. Compared to the double null shape, the lower single null shape is observed to have a lower density, narrower pedestal width, larger density fluctuations over a broad range of wavenumber, and operates closer to the peeling-ballooning instability boundary calculated from the simple pedestal scaling, Δ ψ N, which is still observed to be wider than the EPED prediction.